2009
DOI: 10.1890/07-2146.1
|View full text |Cite
|
Sign up to set email alerts
|

The numerical and functional responses of a granivorous rodent and the fate of Neotropical tree seeds

Abstract: Despite their potential to provide mechanistic explanations of rates of seed dispersal and seed fate, the functional and numerical responses of seed predators have never been explicitly examined within this context. Therefore, we investigated the numerical response of a small-mammal seed predator, Heteromys desmarestianus, to disturbance-induced changes in food availability and evaluated the degree to which removal and fate of seeds of eight tree species in a lowland tropical forest in Belize were related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 52 publications
3
41
1
Order By: Relevance
“…Fixed factors in bold indicate significant differences capita proportion of seeds surviving and the per capita proportion of seeds dispersed at longer distances, which is counterbalanced by mast seeding. Our long-term data from oil tea further support this finding; the per capita proportion (up to 6%) of seeds surviving at caches was higher when seed availability was lower (2002)(2003)(2004)(2005), whereas the per capita proportion (up to 22% in 2007) of seeds surviving at source was higher when seed availability was higher (2006-2009Figs 4 and 6). If the dispersal/survival trade-off exists in predatordispersed plants, non-dispersed seeds near parent plants should also have the potential to establish and recruit as adults (e.g.…”
Section: T H E P R E D a T O R S A T I A T I O N H Y P O T H E S I S supporting
confidence: 72%
See 1 more Smart Citation
“…Fixed factors in bold indicate significant differences capita proportion of seeds surviving and the per capita proportion of seeds dispersed at longer distances, which is counterbalanced by mast seeding. Our long-term data from oil tea further support this finding; the per capita proportion (up to 6%) of seeds surviving at caches was higher when seed availability was lower (2002)(2003)(2004)(2005), whereas the per capita proportion (up to 22% in 2007) of seeds surviving at source was higher when seed availability was higher (2006-2009Figs 4 and 6). If the dispersal/survival trade-off exists in predatordispersed plants, non-dispersed seeds near parent plants should also have the potential to establish and recruit as adults (e.g.…”
Section: T H E P R E D a T O R S A T I A T I O N H Y P O T H E S I S supporting
confidence: 72%
“…Kelly & Sork (2002) suggest that when testing the predator satiation hypothesis, it is essential to quantify how seed predation, seed dispersal and seed survival are related to per capita seed availability, which is determined by annual seed production and annual abundance of seed predators and seed dispersers. To our knowledge, however, few studies have quantified how per capita seed availability varies and the effect that it has on seed fates (but see Klinger & Rejm anek 2009, 2010.…”
mentioning
confidence: 99%
“…(Arecaceae) were determined by seed predation and seed dispersal, and whether the relative rates of seed predation and dispersal varied with alteration in species composition of the seed predator/disperser guild. In the course of previous investigations (Brewer and Rejmánek 1999; Brewer 2001; Klinger 2007; Klinger and Rejmánek 2009) we observed that a large proportion of A . mexicanum nuts were both preyed on and dispersed by the most abundant small mammal in the forest, Heteromys desmarestianus subsp.…”
Section: Introductionmentioning
confidence: 63%
“…These contrasting results reinforces that, besides the probability of discovery, the degree of exploitation need to be taken into account to understand seed removal patterns (Romo et al, 2004). If a seed pile is discovered by predators, it might incur in variable rates of removal according to predator species and its local density, besides the availability of alternative food resources Klinger and Rejmánek, 2009). I documented the lowest intensity of endocarp removal in the edge during the late dry season, a well known period of flesh fruit scarcity in tropical areas (Van Schaik et al, 1993).…”
Section: Discussionmentioning
confidence: 87%